Performance evaluation of hybrid solar chimney for uninterrupted power generation - Al-Kayiem, H.H. (2019)
Solar chimneys have the drawback of being unproductive at night. This study proposed a hybrid solar chimney integrated with an external heat source to complement solar energy for uninterrupted power generation. Flue-gas channels were utilized to supply air into the collector passage. The hybrid arrangement was investigated experimentally and numerically. An experimental model comprising a 6 m-diameter solar air collector, 6.65 m-height chimney, and four flue thermal channels was designed and fabricated. The hybrid system was further simulated using ANSYS-Fluent. The numerical procedure was validated by comparing with experimental measurements for a conventional solar chimney with mean differences of 8.7 and 7.8 in air flow velocity and air temperature rise, respectively. Results showed that the hybrid approach considerably enhanced the plant performance. The insertion of flue channels, even with no flue-gas flow, enhanced the velocity and temperature by 6.87 and 6.3, respectively measured at the chimney base. Simulation results with 0.0015 kg/s at 116 Â°C flue gas in the thermal channels demonstrated that the air-mass flow rate and collector efficiency enhanced by 12.0, and 64.0, respectively. This study proved that the proposed technique can resolve the setback of night operation of solar chimney power plants and enable 24/7 power production. Â© 2018 Elsevier Ltd